Winners and Losers: A Rejoinder to Anne Winter and Matthias Kortmann - Lucassen, Leo; Lucassen, Jan (BMGN - Low Countries Historical Review, 2012)
The criticisms of Anne Winter and Matthias Kortmann of Winners and Losers enable Leo and Jan Lucassen to revise and explain more clearly a number of key arguments of their book. These particularly concern questions about the aim and usefulness of comparisons in time and space. Regarding the spatial comparisons (especially with Germany and Belgium), the authors have tried to show in which respects Dutch migration history is unique and where more general mechanisms were at play. Concerning the comparison of the post-war immigration dynamics with the Early Modern Period, Leo and Jan Lucassen argue that this yields much more than one would assume at first sight. It forces us to think systematically about what is similar and what is different, but it also sheds new light on apparently familiar and unproblematic cases. This response is part of the discussion forum 'Winnaars en verliezers' (Leo Lucassen and Jan Lucassen).